If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + -6x = -21 Solving -9 + -6x = -21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -6x = -21 + 9 Combine like terms: -9 + 9 = 0 0 + -6x = -21 + 9 -6x = -21 + 9 Combine like terms: -21 + 9 = -12 -6x = -12 Divide each side by '-6'. x = 2 Simplifying x = 2
| 8(2n-1)=6(6n+3)+8 | | 3/-4 | | 5p-16=10 | | -7x-12=2x-(5x-8) | | (k-8)/(4+k)=-0.2 | | 7+n/8=n | | 0=a-49 | | ((-3j-(-4))/-6)-8=12 | | -3x+4-2x=7x | | -7-10=3f-10 | | -y/4=-10 | | 16x=0.5 | | -1(z+5)=-1 | | 50+7x-6=13x-4 | | 2x^5/2+5x^3/2=7x^1/2 | | 12=3b-5b | | -7f-10=3f-10 | | 7/1(4/1) | | 7/1(4/1) | | -1(2+5)=-14 | | 53y=2 | | 4n^2-2=14 | | -3n=7n+10 | | 22x+2y=-20 | | 5a+45a+23b+5=25a+3b+56 | | 4/3x=6 | | 15y+10=160+40y | | 96=-6x+5(-x-5) | | 2x(x+1)=7 | | 8p-1+p=10p-9 | | 2z-3=53+9z | | 4+3y=-12 |